O artesanato como alternativa de trabalho e renda: avaliação do Programa Estadual de Desenvolvimento do Artesanato no Munícipio de Aquiraz-Ce - Lemos, Maria Edny Silva (2011)
This study aims to evaluate the socioeconomic impacts of the State Program for Handicraft Development in the quality of life of craftsmen living in Aquiraz County, State of Ceará, from the project design stage to the effective implementation of the program. The Handicraft Development Program aims to coordinate and develop activities focused on the enhancement of the craftsmen, raising their cultural, professional, social and economic levels, and to promote and publicize the Brazilian handicraft. Among the priority lines of action we may mention the generation of employment opportunities and income and the use of regional vocations, encouraging the preservation of local cultures and the formation of an "entrepreneurial" mentality by preparing organizations and their craftspeople to the competitive market. The investigation was realized by the method of case study of two associations in the Municipality of Aquiraz. The results of this study points to the following conclusions: there was no really effective participation of artisans in the development stage of the program; associations of artisans surveyed did not recognize the work of the organs responsible for the program, and at last, it was found that the managers responsible for absence a culture of evaluation of their actio.